2000
DOI: 10.1093/oxfordjournals.jbchem.a022829
|View full text |Cite
|
Sign up to set email alerts
|

Highly Increased Plasma Concentrations of the Nicked Form of  2 Glycoprotein I in Patients with Leukemia and with Lupus Anticoagulant: Measurement with a Monoclonal Antibody Specific for a Nicked Form of Domain V

Abstract: beta(2)-Glycoprotein I (beta(2)GPI) consists of five tandem repeated domains (I, II, III, IV, and V). The nicked form of beta(2)GPI (N-beta(2)GPI ) which was cleaved by plasmin in vitro at Lys 317-Thr 318 in domain V, showed reduced affinity for the negatively charged phospholipids, especially cardiolipin (CL). Recently, the N-beta(2)GPI was detected in the plasma of patients with disseminated intravascular coagulation syndrome (DIC) by an immunological method. In the present study, we prepared monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
0
23
0
2
Order By: Relevance
“…In addition, FXIa cleaves ␤ 2 GPI at Lys 317 -Thr 318 within DV. The cleavage site on ␤ 2 GPI for FXIa is the same as that for plasmin (13)(14)(15). Functional studies demonstrate the significance of maintaining the integrity of the C-terminal loop in DV, because cleavage of DV at Lys 317 -Thr 318 retained the binding of ␤ 2 GPI with FXI but attenuated or abolished the ability of ␤ 2 GPI to inhibit activation of FXI by thrombin (27).…”
Section: Fxia Cleaves ␤ 2 Gpi At Lysmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, FXIa cleaves ␤ 2 GPI at Lys 317 -Thr 318 within DV. The cleavage site on ␤ 2 GPI for FXIa is the same as that for plasmin (13)(14)(15). Functional studies demonstrate the significance of maintaining the integrity of the C-terminal loop in DV, because cleavage of DV at Lys 317 -Thr 318 retained the binding of ␤ 2 GPI with FXI but attenuated or abolished the ability of ␤ 2 GPI to inhibit activation of FXI by thrombin (27).…”
Section: Fxia Cleaves ␤ 2 Gpi At Lysmentioning
confidence: 99%
“…Heparin greatly enhances the plasmin-mediated cleavage of the Lys 317 -Thr 318 site in ␤ 2 GPI at concentrations that can be achieved in vivo during anticoagulation therapy (11). The cleavage at Lys 317 -Thr 318 is generated in vitro by plasmin and at extremely low efficiency by factor Xa (13) and in vivo in pathological states of increased fibrinolysis (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first domain within ␤2-GPI contains a positively charged region that includes Arg 39 , Arg 43 , and Lys 44 . Because it has been reported that this domain binds negatively charged phospholipids, an expression/site-directed mutagenesis approach was used to evaluate the possible importance of this positively charged domain in heparin interaction.…”
Section: Effect Of Heparin On the Plasmin-mediated Cleavage Of ␤2-mentioning
confidence: 99%
“…Thus, it has been proposed that the cleaved form of ␤2-GPI is probably generated during normal fibrinolysis. More recently, the presence of the processed form of ␤2-GPI was demonstrated in patients with leukemia and with lupus anticoagulant activity (39). It was proposed that plasmin is the likely protease that generates the proteolytically processed form of ␤2-GPI.…”
Section: Figmentioning
confidence: 99%